The role of autophagy in Parkinson’s disease: a gender difference overview - Cucinotta, Laura; Mannino, Deborah; Filippone, Alessia; Romano, Adele; Esposito, Emanuela; Paterniti, Irene (Frontiers in Pharmacology, 2024)
Recent studies have demonstrated dysregulation of the autophagy pathway in patients with Parkinson's disease (PD) and in animal models of PD, highlighting its emerging role in disease. In particular, several studies indicate that autophagy, which is an essential degradative process for the damaged protein homeostasis and the management of cell balance, can manifest significant variations according to gender. While some evidence suggests increased autophagic activation in men with PD, women may have distinct regulatory patterns. In this review, we examined the existing literature on gender differences in PD-associated autophagic processes, focusing on the autophagy related proteins (ATGs) and leucine rich repeat kinase 2 (LRRK2) genes. Also, this review would suggest that an indepth understanding of these gender differences in autophagic processes could open new perspectives for personalized therapeutic strategies, promoting more effective and targeted management of PD.